Style and Meaning in Laura Art: A case Study in the Formal Analysis of Style in Prehistoric Art - Rosenfeld, Andrée (The Australian journal of anthropology, 1982)
The objective identification of animals depicted in the rock art of the Laura region frequently presents problems. An analysis of the combinations of zoologically diagnostic traits represented and of trends in body outline reveals that animal figures were drawn as fairly conventionalized schema. By analogy with contemporary Aboriginal art systems it is unlikely that the artists intended to paint generalized animal images, and it is suggested that other, possibly non-visual information may have been encoded in the Laura rock art system which enabled Aboriginal people to identify the paintings. A preliminary analysis of the distribution of paintings in some shelter groups of Laura art suggest that the identity of the shelter is likely to have been one of the factors involved in determining the species represented. This suggestion gains some support from the paintings of introduced animals, for which now and diagnostic artistic conventions were devised. The apparently greater need for explicit rendition of introduced species might be explained by the fact that traditional modes for image recognition could not be applied to these newcomers.